PENINGKATAN KEMAMPUAN BERSOSIALISASI SISWA KELAS V MELALUI METODE SOSIODRAMA PADA MATA PELAJARAN TEMATIK TEMA 8 SUBTEMA 1 PEMBELAJARAN 3 DI MI KELOPO TELU DESA KAPU KECAMATAN MERAKURAK TAHUN PELAJARAN 2020/2021 - Ninik Hidayati; Nurul Hakim; Wildatul Hikmah (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
The problem of this research is to explain about increasing students' social skills in thematic subjects of theme 8 sub-theme 1 through the sociodrama method at MI Kelopo Telu, Kapu Village, Merakurak District, 2020/2021 Academic Year. The theories that are used as the basis in the implementation of this research include the theory of students' social skills, the advantages and disadvantages of the sociodrama method, and the learning process using the sociodrama method. Based on the background of the problem, this research is expected to provide answers to the formulation of the problem (1) How is the process of socializing MI students to improve students' social skills through the sociodrama method on thematic subjects theme 8 sub-theme 1 learning 3 class V students at MI Kelopo Telu academic year 2020 /2021? (2) What are the advantages and disadvantages of implementing the sociodrama method to improve students' social skills through the sociodrama method in thematic subjects of theme 8 sub-theme 1 learning 3 class V at MI Kelopo Telu for the 2020/2021 school year? (3) How is the application of the sociodrama method in improving students' social skills through the sociodrama method on thematic subjects of theme 8 sub-theme 1 learning 3 for fifth grade students at MI Kelopo Telu Kapu for the 2020/2021 academic year? Based on the formulation of the problem, this researcher aims (1) to find out the socialization process of MI students to improve students' social skills through the sociodrama method on thematic subjects of theme 8 sub-theme 1 learning 3 class V at MI Kelopo Telu for the academic year 2020/2021 (2) To find out improvement of students' ability to socialize after the sociodrama method on thematic subjects of theme 8 sub-theme 1 learning 3 which is applied in class V MI Kelopo Telu for the academic year 2020/2021. (3) To find out the advantages and disadvantages of implementing the sociodrama method in thematic subjects of theme 8 sub-theme 1 learning 3 to improve the social skills of fifth grade students of MI Kelopo Telu for the 2020/2021 academic year.